Cost evaluation of different medium solids for air dense medium fluidized bed coal separation - Chagwedera, Kundayi Marshall (My University, 2017)
Dense medium processing of high-ash coals with liquid dense media water and magnetite is currently the conventional means of beneficiating coal in South Africa SA. Hence, large volumes of waste water are produced along with a high cost of treating this effluent, both factors of which constitute a major disadvantage to this technique. This study presents an experimental account of Air Dense Medium Fluidized Bed ADMFB as an alternative dry processing approach for beneficiating SA coals. Magnetite is the conventional medium in ADMFB application this medium material is costly and limited in quantity. Pyrrhotite, granulated blast-furnace slag, silica sand and coal discards were investigated as alternative air dense medium materials to either replace or augment magnetite.
A research report submitted in fulfilment of the requirements for the degree of Master of Science in Engineering to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, Johannesburg, South Africa, University of the Witwatersrand, Johannesburg, 2017